Alfred Schutz's Phenomenological Analysis of Community Social Behavior in Responding to Cooking Oil Scarcity - Encup Supriatna (International Journal of Science and Society, 2022)
The purpose of this study was to analyze the community's social behavior in responding to the scarcity of cooking oil using the phenomenological point of view developed by Alfred Schutz. This study uses a qualitative method with a phenomenological framework approach because it focuses on exploring the experience and meaning of phenomena to gain learning in a multicultural society. This study uses two types of data: primary and secondary data. Preliminary data were collected through interviews with five people through a random purposive sampling method, while secondary data were collected through literature studies. The research was conducted in January 2022. According to Alfred Schutz, phenomenological analysis demands the discovery of the world that follows what is experienced by the person concerned. The meaning is divided into several views, and some subjects interpret the phenomenon of panic buying as caused by the actions of the oligarchs who are not in favor of the community, as an indicator of the government's lack of seriousness in balancing market prices in the community, or also interpreted as another effect of the pandemic which has disrupted the economic sector.